Marriage decision making, spousal communication, and reproductive health among married youth in Pakistan - Saima Hamid; Rob Stephenson; Birgitta Rubenson (Taylor & Francis Group, 2011)
Background: Married young women's reproductive needs are a challenge in traditional Pakistani society. The decisions regarding family planning and pregnancy are controlled by the family, often involving complex negotiations. The current study was undertaken to explore how young married women's involvement in the arrangements surrounding their marriage is associated with their ability to negotiate sexual and reproductive health decisions in marriage. Objective: The study explores the associations between young women's involvement in their marriage arrangements and their ability to negotiate for contraceptive use and fertility decisions. Methodology: A subset of 1,803 married young women aged 15–24 years was drawn from a nationally representative adolescent and youth survey conducted in Pakistan in 2001–2002 by the Population Council. Regression models were fitted to outcomes: reported agreement with spouse on the number of children to have, current use of contraceptives, intention to use contraceptives in the future, and the time elapsed between marriage and first contraceptive use. Key covariates of interest were variables that measure the involvement of young women in their marriage: (a) having a say in selection of spouse, (b) having met him prior to marriage, and (c) whether he was related to respondent's family. Other factors explored were respondents’ mobility outside of household, social role, and decision making in their homes. Results: Having a say in the selection of a spouse was significantly associated with agreement with spouse over number of children to have, intention to use contraceptives, and the time between marriage and first contraceptive use. These relationships existed after controlling for education, socioeconomic status, mobility outside of house, and decision making in the home. Discussion : Women who had decision-making freedom in their parental home carried this ability with them into marriage in their new home and were better able to negotiate about their fertility.